2016
DOI: 10.15171/jcvtr.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

Tetralogy of Fallot and pheochromocytoma in a situs inversus totalis: An unusual association

Abstract: Introduction: Situs inversus totalis is an uncommon anomaly which exist a complete transposition of organs and it’s occasionally associated with congenital heart diseases, such as tetralogy of fallot. Pheochromocytoma is a rare neuroendocrine tumor with an annual incidence of 2-8 cases per million people and for years has been studied its relationship with the hypoxic pathway. Case Report: A 29 year old male with a history of tetralogy of fallot corrected at 10 years and situs inversus totalis. He was admitte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…PHEO or PGL is a catecholamine‐producing tumor that arises from sympathetic lineage–derived cells of the adrenal medulla or the extra‐adrenal paraganglia . Cyanotic congenital heart disease (CHD) was speculated to be associated with PHEO/PGL because of case reports of PHEO/PGL that developed in relatively young patients with cyanotic CHD . Opotowsky et al recently reported that patients with cyanotic CHD had increased odds ratio (6.0; confidence interval, 2.6–13.7; P < 0.0001) for PHEO/PGL development compared with those without cyanotic CHD in a multicenter case series …”
Section: Introductionmentioning
confidence: 99%
“…PHEO or PGL is a catecholamine‐producing tumor that arises from sympathetic lineage–derived cells of the adrenal medulla or the extra‐adrenal paraganglia . Cyanotic congenital heart disease (CHD) was speculated to be associated with PHEO/PGL because of case reports of PHEO/PGL that developed in relatively young patients with cyanotic CHD . Opotowsky et al recently reported that patients with cyanotic CHD had increased odds ratio (6.0; confidence interval, 2.6–13.7; P < 0.0001) for PHEO/PGL development compared with those without cyanotic CHD in a multicenter case series …”
Section: Introductionmentioning
confidence: 99%
“…Secondly, significant pulmonary regurgitation is almost always encountered following a transannular patch repair and although it is usually well tolerated for years it finally leads to symptomatic right ventricular dilation and dysfunction moreover if it coexists with significant tricuspid regurgitation. Both valvular pathologies are suspected, although pulmonary regurgitation is not mentioned, in the patient reported by Tapia-Orihuela et al 1 according to their echocardiographic and auscultatory data. When valvular regurgitations are severe, pulmonary valve replacement and tricuspid annuloplasty should be performed before irreversible right ventricle dysfunction ensues.…”
Section: Dear Editormentioning
confidence: 93%
“…We have read with interest the article published by Tapia-Orihuela et al 1 However, in the wake of that reading, we would like to make a few comments that we believe to be important.…”
Section: Dear Editormentioning
confidence: 99%